2021
DOI: 10.3389/fpls.2021.628251
|View full text |Cite
|
Sign up to set email alerts
|

High Drying Temperature Accelerates Sunflower Seed Deterioration by Regulating the Fatty Acid Metabolism, Glycometabolism, and Abscisic Acid/Gibberellin Balance

Abstract: Sunflower seed storage is accompanied by the loss of seed vigor. Seed drying is a key link between seed harvest and seed storage; however, to date, the effect of seed drying on sunflower seed deterioration during storage remains unclear. The present study performed hot air drying for sunflower seeds with an initial moisture content of 30% to examine the manner in which drying temperature (35, 40, 45, 50, and 55°C) affects the drying performance and seed vigor following storage process (6 and 12 months). A dryi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 61 publications
1
9
0
Order By: Relevance
“… 63 According to research on accelerated aging sunflower seeds, the soluble sugar, fructose, and sucrose levels in sunflower seeds were dramatically reduced after 12 months of storage. 21 Moreover, the study of the variations in sugar concentration in aging safflower seeds discovered that sucrose content decreased slowly with age whereas raffinose and monosaccharides content reduced rapidly at 10 days. 64 This observation of sucrose reduction was consistent with the results of our study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 63 According to research on accelerated aging sunflower seeds, the soluble sugar, fructose, and sucrose levels in sunflower seeds were dramatically reduced after 12 months of storage. 21 Moreover, the study of the variations in sugar concentration in aging safflower seeds discovered that sucrose content decreased slowly with age whereas raffinose and monosaccharides content reduced rapidly at 10 days. 64 This observation of sucrose reduction was consistent with the results of our study.…”
Section: Discussionmentioning
confidence: 99%
“…The study on sunflower seeds reported that high temperatures can cause seed stress and enzyme activity dysregulation. It may reduce seed vigor by suppressing storage substance catabolism in the seed endosperm . The report of the maize seed artificial aging study revealed that the germination energy, germination rate, and stress-related enzyme activities were reduced during artificial aging .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the seeds storage, the decrease of activities of antioxidant enzymes, lipid peroxidation, and substantial accumulation of ROS, MDA resulted in the deterioration of seed vigor ( Corbineau and Bailly, 2007 ). Our previous study reported that naturally aging significantly increased the accumulations of H 2 O 2 , O 2 ⋅ – , and MDA and resulting in the acceleration of seed deterioration ( Huang et al, 2021b ). ROS has a dual function, which plays a positive role in seed development, germination, and resistance to environmental stress at appropriate concentrations, while generating toxic effects on the cells and plant tissues at excessive concentrations ( Barba-Espin et al, 2011 ; Oracz et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Reducing grain moisture levels can improve grain quality and influence the formation of grain contains, flavor, color, acidity, and chemical content [1]- [6]. Furthermore, the drying process is also used on many agricultural products, such as ginger [7], soybean [8], coffee bean [9], cocoa bean [10], pumpkin seeds [11], sunflower seeds [12], and many more.…”
Section: Introductionmentioning
confidence: 99%